Restorative Justice Regulations in Reforming Criminal Procedure Law - Andry Syafrizal Tanjung; Jafan Fifaldi Harahap (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
The aim of this research is to determine restorative justice regulations in reforming criminal procedure law. This research is legal research with juridical-normative characteristics to gain an understanding of law at a normative level and its implementation at a practical level using Roscoe Pound's legal theory approach where law is a tool of social engineering. Various questions that arise in this research will be analyzed from the perspective of Roscoe Pound’s theories. The practice of dispute resolution involving the affected parties and the community has actually been widely implemented in Indonesia. In fact, dispute resolution outside the formal judicial process was carried out long before the Indonesian state was formed.